2015
DOI: 10.1103/physrevb.92.020408
|View full text |Cite|
|
Sign up to set email alerts
|

Towards graded-index magnonics: Steering spin waves in magnonic networks

Abstract: Magnonics explores precessional excitations of ordered spins in magnetic materials-so-called spin wavesand their use as information and signal carriers within networks of magnonic waveguides. Here, we demonstrate that the nonuniformity of the internal magnetic field and magnetization inherent to magnetic structures creates a medium of graded refractive index for propagating magnetostatic waves and can be used to steer their propagation. The character of the nonuniformity can be tuned and potentially programmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 47 publications
(106 reference statements)
0
78
0
Order By: Relevance
“…Furthermore, recent experimental studies showed an efficient spin-wave electrical tuning in thin magnetic films, such as YIG (Y 3 Fe 5 O 12 ) [4]. At present, interest to such phenomena is very active due to their potential applications in magnon spintronics and magnonics [7][8][9], where an electrically controlled phase shifter for spin waves could become an essential component of spin-wave devices. Nonreciprocity and unidirectionality of spin-wave propagation would be also valuable for this purpose [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent experimental studies showed an efficient spin-wave electrical tuning in thin magnetic films, such as YIG (Y 3 Fe 5 O 12 ) [4]. At present, interest to such phenomena is very active due to their potential applications in magnon spintronics and magnonics [7][8][9], where an electrically controlled phase shifter for spin waves could become an essential component of spin-wave devices. Nonreciprocity and unidirectionality of spin-wave propagation would be also valuable for this purpose [10].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is capable of exciting both magneto-dipole and dipole-exchange spin waves, depending on the frequency of excitation and / or the film thickness. Furthermore, the uniformity of the exciting magnetic field implies that the excitation could also accompany such common measurement techniques of magnonics as cavity and waveguide based ferromagnetic resonance spectroscopy [28], time-resolved scanning Kerr microscopy [1] and microwave assisted Brillouin Light Scattering imaging [14], [20].…”
Section: Resultsmentioning
confidence: 99%
“…HE PATTERNING of magnetic nanostructures, in order to steer [1]- [3], modulate [4], [5], or otherwise modify [6], [7] the properties of propagating spin waves, has led to the successful design of many elements of perceived magnonic computing architecture [8]- [12]. Indeed, it has been predicted [13] that this progress could eventually lead to the use of spin waves as information carriers within future data processing and communication technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Electrically measured spin-wave transmission characteristics of straight YIG stripes of 470 μm width and DB-05 7.5 μm thickness magnetized by a field of 1160 Oe revealed that the propagation of spin waves was most efficient at frequencies between 5.16 and 5.45 GHz [18]. BLS was used to image spin waves propagating at the frequency of 5.26 GHz through the multiplexer magnetized by the field of the same value applied at 7° to the leg length.…”
Section: Resultsmentioning
confidence: 99%